Respuesta :
Answer:
(C) [tex]8x^{a+b} + 4x^{a+3} - 10x^{a+1}[/tex]
Step-by-step explanation:
[tex]-2x^a(-4x^b -2x^3 +5x)=-2x^a(-4x^b)-2x^a(-2x^3)-2x^a(5x)=\\\\=8x^{a+b} + 4x^{a+3} - 10x^{a+1}[/tex]
Answer: The correct option is
(C) [tex]8x^{a+b}+4x^{a+3}-10x^{a+1}.[/tex]
Step-by-step explanation: We are given to find the following product :
[tex]P=-2x^a(-4x^b-2x^3+5x)~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
We will be using the following property of exponents :
[tex]x^a\times x^b=x^{a+b}.[/tex]
From (i), we get
[tex]P\\\\=-2x^a(-4x^b-2x^3+5x)\\\\=(-2x^a)\times(-4x^b)-2x^a\times(-2x^3)-2x^a\times5x\\\\=8x^{a+b}+4x^{a+3}-10x^{a+1}.[/tex]
Thus, the required product is [tex]8x^{a+b}+4x^{a+3}-10x^{a+1}.[/tex]
Option (C) is CORRECT.